Fizik kuantum: kuasa berfikir membentuk keseimbangan tenaga / Siti Aminah Mohammad - Mohammad, Siti Aminah (Universiti Teknologi MARA, Sabah, 2019)
Humans are created in the best of nature, and to distinguish humans from other beings are minds. In terms of science, the human body consists of cells; the cells are composed of molecules and the molecules are made up of atoms and eventually the atom is composed of sub-atoms (energy). When viewed from the atomic level, humans are the same as other creatures, the difference is only at the rate of atomic vibrations. Everything in the world has a vibration that will balance the amount of energy in the universe. This concept paper basically explains the existence of energy for body or object in quantum physics, and to look into the concept of power of thinking in energy balance. Data or information in the concept paper uses secondary data from related journals, books and websites. With this concept paper, it helps in understanding the impact of human thought in our daily lives.